Cultures of childhood: A look at quilombo children - Alves dos Santos, Maria Tarcília; Araújo e Silva, Margareth (Guará Journal, 2024)
The   project   “Quilombola   Community:   Identity   constitution   and  school  and  non-school  formative  experiences”,  registered  in  the  Extension Information  System  of  the  Federal  University  of  Goiás  –  Jataí  Regional  (PI0116-2016),  was  developed  in  the  Quilombola  Community  of  Cedro,  located  in  the  Municipality  of Mineiros, State of Goiás. The study followed the regulations of the Ethics Committee for Research Involving Human Beings (CAAE  nº 62116416.9.0000.5083,  em  conformidade  com  o  precer  consubstanciado  nº  1.864.576).  This  work  sought  to  un-derstand  the  identity  composition  and  school  and  non-school  training experiences of a group of subjects living in the Quilom-bola  do  Cedro neighborhood,  Mineiros,  Goiás,  based  on  data  collected  between  the  years  2016  and  2022.  Considering  that  we start from paradigms of Psychology and Education, two fiel-ds that have only recently become interested in ethnic studies, it was necessary to complement the theoretical subsidies that support  this  extension  project  with  anthropological  knowled-ge.  Thus,  the  results  are  the  result  of  the  connection  between  anthropological,  psychological  and  pedagogical  knowledge.  Deepening theoretical research was important, especially with regard to contextualized human development based on Bron-frenbrenner’s (1996) ecological development theory, which hel-ped create a paradigm shift  in educational psychology. Among the results, we highlight the verification of oral culture as a way of  transmitting  knowledge  and  values;  the  relationship  with  the  land  and  nature  as  an  important  non-school  training  ex-perience;  capoeira,  an  activity  very  present  in  the  community,  as  a  sporting  practice  and  also  a  form  of  cultural  expression;  as well as the recognition that within each Quilombola child in Cedro, there is a rich social, cultural and historical construction, resulting from a unique and special interpretation that calls for attention and appreciation.
Keywords: Cultures of childhood; Ecological development; Quilombola children